Understanding forest pictures on social media– A method to grasp nonverbal dimensions of human–nature relationships. Issue 4 (2nd October 2021) - Breithut, Jasmin; Hebermehl, Wiebke; Bethmann, Stephanie; Wirth, Kristina
ABSTRACT: The increasing importance of images as an everyday medium of communication (e.g. in consequence of the use of smartphones and social media) has led to an intensive engagement of the social sciences with the methodological accessibility of images. In this paper we present a qualitative image analysis method developed to understand nonverbal dimensions of human-nature relationships. The method is methodologically substantiated and presented in form of a step-by-step guideline. It offers an opportunity to transfer images into words by accepting the images characteristic materiality. Furthermore, an example analysis of a picture posted on a social media platform is provided. Based on this, this paper asks and discusses what research dedicated to the visual can do for environmental sociology regarding content-related insights as well as regarding methodological issues addressing a sociological research that rethinks and expands its repertoire to increasingly involve more-than-human actors in environmental sociology. In this way, the paper aims to discuss the added value of the suggested method and its potential to improve the understanding of sensory and emotional dimensions of human-nature relationships in the context of environmental sociology.